'Data.gov-in-a-box': Delimiting transparency. (May 2015) - Birchall, Clare
Given that the Obama administration still relies on many strategies we would think of as sitting on the side of secrecy, it seems that the only lasting transparency legacy of the Obama administration will be data-driven or e-transparency as exemplified by the web interface 'data.gov '. As the data-driven transparency model is exported and assumes an ascendant position around the globe, it is imperative that we ask what kind of publics, subjects, and indeed, politics it will produce. Open government data is not just a matter concerning accountability but is seen as a necessary component of the new 'data economy'. To participate and benefit from this info-capitalist-democracy, the data subject is called upon to be both auditor and entrepreneur. This article explores the implications of responsibilization, outsourcing, and commodification on the contract of representational democracy and asks if there are other forms of transparency that might better resist neoliberal formations and re-politicize the public sphere.